Tandem catalysis method for improving catalytic efficiency of preparing higher alcohol by CO2 hydrogenation
By using a two-stage fixed bed reactor series method in the process of hydrogenating CO2, the olefin catalyst and olefin hydroformylation catalyst are prepared by hydrogenating CO2, the problems of selectivity and low temporal and spatial yield of higher alcohols in the prior art are solved, and high-efficiency high-alcohol generation and carbon utilization are achieved.
Patent Information
- Application Number
- CN202411643746.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
The existing catalyst system for preparing advanced alcohols for CO2 hydrogenation has problems of selectivity and low temporal and spatial yields, and it is difficult to effectively improve the catalytic efficiency of CO2 hydrogenation to produce advanced alcohols.
Using the method of two-stage fixed bed reactors in series, the first stage reactor is filled with CO2 and hydrogenated to prepare an olefin catalyst, and the second stage reactor is filled with olefin hydrogenation catalyst and aldehyde hydrogenation to prepare an alcohol catalyst, so as to improve the efficiency of advanced alcohol generation through the tandem catalytic process.
It significantly improves the selectivity and spatiotemporal yield of higher alcohols, increases the utilization rate of carbon atoms, reduces the separation cost of products, and is suitable for industrial applications.
Abstract
Description
Technical Field
[0001] The invention relates to a method for improving the catalytic efficiency of preparing higher alcohols by hydrogenation of CO2, and in particular to a series catalytic method for improving the catalytic efficiency of preparing higher alcohols by hydrogenation of CO2. Background Art
[0002] Higher alcohols are alcohols with a carbon number greater than 2 (abbreviated as C 2+ alcohol) C 2+ Alcohol has high energy density, safe transportation and good gasoline blending performance. It can be used as a fuel additive or directly as a clean fuel. 2+ Alcohols can be used as chemical intermediates or platform molecules to transform into downstream products, such as synthetic polymers, olefins, disinfectants, detergents, etc. Using CO2 as the carbon and oxygen source, C 2+ Alcohol, is a synthetic C 2+ The new green route to alcohol is expected to become a potential alternative to coal / petroleum or biofermentation routes. At the same time, due to the similar characteristics to the synthesis gas conversion reaction, the future CO2 catalytic hydrogenation process can be directly carried out on the synthesis gas conversion industrial unit, which is convenient for industrial application.
[0003] Typical CO2 hydrogenation to C 2+ Catalyst systems for alcohols include precious metal systems (including Rh, Pt, Ir, Pd, etc.) and non-precious metal systems (including modified copper-based methanol synthesis catalysts, modified Fischer-Tropsch synthesis catalysts, and modified molybdenum-based catalysts), and the corresponding reactors include tank reactors and fixed-bed reactors. These catalysts still have the problems of low selectivity (10-20%) and low space-time yield (<200 mg / g / h) for higher alcohols. In addition, the preparation of higher alcohols by hydrogenation of CO2 is a multi-step cascade process, and there are also many side reactions. Therefore, it is difficult to break through the reaction bottleneck of low efficiency and low yield of CO2 hydrogenation to produce higher alcohols only by regulating the active sites of the catalyst.
[0004] The document Revealing and Regulating the Complex Reaction Mechanism of CO2Hydrogenation to Higher Alcohols on Multifunctional Tandem Catalysts (ACSCatal., 2023) discloses the formation of a tandem catalytic system of Co2C and CuZnAl in a reactor, with the aim of improving the efficiency of CO2 hydrogenation to produce higher alcohols. Among them, Co2C is used for CO2 hydrogenation to produce olefins, and CuZnAl is used for CO2 hydrogenation to produce methanol. Two reactions need to be carried out simultaneously. The olefins produced by Co2C are hydrogenated on the surface of CuZnAl to produce CHx intermediates, which are coupled with the CHO intermediates produced by CuZnAl at CuZnAl to form alcohols. This method utilizes the coupling between reaction intermediates during the reaction process, which has high requirements for the catalyst, especially the need for multifunctional catalytic active sites. The matching of reaction rates at different sites is the key to achieving high selectivity for higher alcohols. Therefore, the catalyst system obtained by this design idea still has a large proportion of by-products (especially alkanes, methanol, etc.) in its products. The optimal catalyst under the optimal conditions of this method showed a selectivity and space-time yield of higher alcohols of 18.3% and 2.2 mmol / g / h, respectively. 3+ The proportion of alcohol can only reach 33%, mainly ethanol. In addition, the proportion of methanol can reach 6-60%. Summary of the invention
[0005] The purpose of the present invention is to provide a tandem catalytic method for improving the catalytic efficiency of CO2 hydrogenation to produce higher alcohols, which solves the problems of low selectivity and low space-time yield of the existing CO2 hydrogenation to produce higher alcohols, can significantly improve the selectivity and space-time yield of higher alcohols, and at the same time increase the utilization rate of carbon atoms, reduce the separation cost of the product, and easily realize industrial application.
[0006] In order to achieve the above-mentioned object, the present invention provides a series catalytic method for improving the catalytic efficiency of CO2 hydrogenation to produce higher alcohols, the method comprising: using two fixed bed reactors in series, the first reactor is filled with CO2 hydrogenation to produce olefins catalyst, and the second reactor is filled with olefin hydroformylation catalyst and aldehyde hydrogenation to produce alcohol catalyst in sequence.
[0007] Preferably, the CO2 hydrogenation to olefins catalyst is selected from any one or two of an iron-based hydrogenation catalyst and an oxide@SAPO-34 composite catalyst; when the catalyst contains an oxide@SAPO-34 composite catalyst, in the first stage reactor, the CO2 hydrogenation to olefins controls the volume ratio of the obtained CO to olefins to be greater than 1.
[0008] Preferably, the iron-based hydrogenation catalyst is selected from a carbon-coated iron-based catalyst; the iron-based catalyst is a carbon-coated iron oxide loaded with an alkali metal or an alkali metal and nickel; wherein the nickel loading is 0 to 3 wt% and the alkali metal loading is 0.5 to 5 wt%; or / and, the oxide@SAPO-34 composite catalyst is selected from a zinc-zirconium oxide@SAPO-34 composite catalyst.
[0009] The carbon-coated iron-based catalyst of the present invention, while catalyzing the hydrogenation of CO2 to produce higher alcohols, also produces a large amount of olefins. The present invention further converts the olefins into aldehydes / alcohols in a series manner, which can further improve the production efficiency of higher alcohols and the utilization rate of carbon.
[0010] Preferably, the alkali metal loading is 4 to 5 wt%.
[0011] Preferably, in the carbon-coated iron-based catalyst, the alkali metal is selected from at least one of Li, Na, K, Rb and Cs.
[0012] Preferably, the carbon-coated iron-based catalyst is obtained by the following method: impregnating and modifying ferric oxide with an alkali metal salt, or impregnating and modifying ferric oxide with a nickel salt and an alkali metal salt in sequence, and then introducing an inert gas containing CO for reduction and carbonization treatment; or / and, the zinc-zirconium oxide@SAPO-34 composite catalyst is obtained by the following method: grinding zinc-zirconium oxide and SAPO-34 in a mass ratio of 1:2.
[0013] Preferably, the carbon-coated iron-based catalyst is obtained by the following method: using nickel salt as a precursor, first introducing nickel into ferric oxide by an impregnation method, and obtaining a nickel-modified ferric oxide catalyst after drying and calcining at 400°C for 6h; then, using potassium salt as a precursor, introducing potassium into the nickel-modified ferric oxide by an impregnation method, and then calcining at 350°C for 6h under flowing air conditions to obtain an iron-based catalyst; then, in an inert gas containing CO, carbonizing at 350°C for 5h to obtain a carbon-coated iron-based catalyst; or / and, the zinc-zirconium oxide@SAPO-34 composite catalyst is obtained by the following method: 1) preparing zinc-zirconium oxide by a citric acid sol method, wherein the molar ratio of Zn / Zr in the oxide is 3 / 1; 2) SAPO-34 is synthesized by a hydrothermal method: aluminum isopropoxide powder is slowly added to an aqueous solution of tetraethylammonium hydroxide and stirred until the aluminum isopropoxide is completely hydrolyzed; under stirring, a phosphoric acid solution with a mass fraction of 85% is added to the solution; after all the phosphoric acid is added, stirring is continued for 2 hours; finally, 40wt% silica sol is added dropwise and stirring is continued for 1 hour to form a uniform solution; finally, the obtained gel solution is transferred to a reactor and crystallized at 170°C for 3 days; the obtained sample is repeatedly washed with deionized water and ethanol, and a solid sample is obtained by centrifugation; the solid sample is dried at 80°C; finally, the prepared solid is calcined at 600°C in a muffle furnace for 6 hours; 3) zinc zirconium oxide and SAPO-34 are ground in a mass ratio of 1:2.
[0014] More preferably, zinc zirconium oxide is prepared by a citric acid sol method, comprising: dissolving Zn(NO3)2·6H2O and Zr(NO3)4·5H2O in water, then adding monohydrated citric acid, stirring at room temperature, and then stirring at 80°C until a gel is formed, and calcining the formed gel at 500°C in a muffle furnace.
[0015] Preferably, when the CO2 hydrogenation catalyst for preparing olefins is selected from a carbon-coated iron-based catalyst, an iron-based catalyst is installed in the first-stage reactor, and the carbon-coated iron-based catalyst is obtained by carbonization treatment. When the temperature of the first-stage reactor is controlled to be a catalytic reaction temperature of 300-350°C, a mixture of 3.0MPa, 2000-8000mL / g / h CO2 and H2 is introduced as a reaction gas for reaction; at the same time, the second-stage reactor is heated to the desired reaction temperature; when the CO2 hydrogenation catalyst for preparing olefins is selected from an oxide@SAPO-34 composite catalyst, the first-stage reactor is pretreated by introducing Ar at a flow rate of 50mL / min and normal pressure at 400°C; then the temperature is reduced to 380°C for the catalytic reaction temperature in a 50mL / minAr atmosphere, and a mixture of 3.0MPa, 20mL / min CO2 and H2 is introduced as a reaction gas for reaction; at the same time, the second-stage reactor is heated to the desired reaction temperature.
[0016] Preferably, the reactor is a fixed bed reactor.
[0017] More preferably, when the CO2 hydrogenation to olefins catalyst is selected from a carbon-coated iron-based catalyst, in a fixed bed reactor prepared with the carbon-coated iron-based catalyst, the temperature is lowered to the catalytic reaction temperature after carbonization, and a mixture of CO2 and H2 at 3.0 MPa and a reaction space velocity of 8000 mL / g / h is introduced as a reaction gas to carry out the CO2 hydrogenation to olefins reaction.
[0018] Preferably, in the reaction gas, the volume ratio of CO2 to H2 is 1:3.
[0019] Preferably, the olefin hydroformylation catalyst is selected from a phosphorus-containing polymer or an oxide-supported highly dispersed Rh catalyst, and its Rh loading is 0.1wt%; or / and, the aldehyde hydrogenation catalyst to prepare alcohol is selected from an oxide-supported Cu-based catalyst, and its active Cu loading is 10wt%.
[0020] More preferably, the Cu-based catalyst supported by the oxide carrier is a Cu / SiO2 catalyst.
[0021] More preferably, the Cu / SiO2 catalyst is prepared by an impregnation method, comprising: adding gaseous SiO2 to a Cu(NO3)2 aqueous solution, stirring, and then heating at 80°C to remove water; grinding the resulting powder and calcining it at 450°C in a muffle furnace; and reducing the calcined sample at 300°C for 4h.
[0022] More preferably, the specific surface area of the gas phase SiO2 is 300m 2 / g.
[0023] More preferably, in the preparation of the Cu / SiO2 catalyst, reduction is performed using 10% H2 / Ar at a gas flow rate of 50 mL / min.
[0024] More preferably, the phosphorus-containing polymer or oxide-supported highly dispersed Rh catalyst is selected from Rh / POLs or Rh / CeO2.
[0025] More preferably, the Rh / CeO2 is prepared by an impregnation method, comprising: dissolving RhCl3 in water, then adding CeO2, stirring and ultrasonicating at room temperature, and then heating at 80°C to remove water; grinding the obtained powder and calcining it at 400°C in a muffle furnace; then reducing the calcined sample at 250°C
[0026] More preferably, in the preparation of Rh / CeO2, reduction is performed using 10% H2 / Ar at a gas flow rate of 50 mL / min.
[0027] More preferably, the preparation of Rh / CeO2 adopts CeO2 prepared by a hydrothermal method, comprising: quickly adding an aqueous NaOH solution to an aqueous Ce(NO3)3 solution, stirring, and then treating at 100°C in a hydrothermal kettle; the product is dried at 80°C after centrifugal washing, and the dried solid is calcined at 600°C in a muffle furnace.
[0028] Preferably, the olefin hydroformylation catalyst and aldehyde hydrogenation catalyst are sequentially loaded into the second stage fixed bed and separated by inert fillers, the reaction temperature is 150-170°C, the raw material at the reactor inlet is the outlet gas of the first stage reactor, and the reaction pressure and gas flow rate are the same as those of the first stage reactor.
[0029] More preferably, the inert filler is quartz wool.
[0030] The tandem catalytic method for improving the catalytic efficiency of CO2 hydrogenation to produce higher alcohols of the present invention solves the problems of low selectivity and low time-space yield of the existing CO2 hydrogenation to produce higher alcohols, and has the following advantages:
[0031] (1) The present invention performs segmented catalysis on the complex CO2 hydrogenation process to prepare higher alcohols. The CO2 hydrogenation catalyst to prepare olefins, the hydroformylation catalyst and the aldehyde hydrogenation catalyst are installed in the upstream and downstream reactors respectively, in order to improve the efficiency and selectivity of CO2 hydrogenation to prepare higher alcohols. The series catalysis can effectively reduce the selectivity of by-product hydrocarbons, improve the utilization rate of carbon, significantly increase the selectivity and space-time yield of higher alcohols, and reduce the separation cost of the product.
[0032] (2) In the tandem catalytic process of the present invention, the ratio of olefins to CO in the first stage product is controlled, the selectivity of higher alcohols is high (>45%), the space-time yield of higher alcohols is high (>300 mg / g / h), and the reaction conversion rate is high (>10%);
[0033] (3) The hydroformylation process of the present invention can add one carbon, and the C 3+ The proportion of alcohol can reach more than 50%, and the proportion of methanol is less than 3%;
[0034] (4) The synthesis technology of each stage catalyst used in the present invention is mature, which is convenient for large-scale preparation and industrial application;
[0035] (5) The two-stage reactors of the present invention are independent of each other, the temperature can be controlled by the heating furnace of each stage reactor, and the pressure can be regulated by the pressure controller of the first stage reactor. The two-stage reactors are in series mode with the same pressure. The method of the present invention is simple to operate and can be easily implemented in industrial applications. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] It should be noted that if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased from the market.
[0038] In the present invention, all features defined in the form of numerical ranges or percentage ranges, such as values, quantities, contents and concentrations, are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0039] The features mentioned in the present invention can be combined arbitrarily, as long as there is no contradiction in the combination of these features, all possible combinations should be considered as the scope of this specification. Each feature disclosed in the specification can be replaced by any alternative feature that can provide the same, equal or similar purpose. Therefore, unless otherwise specified, the disclosed features are only general examples of equal or similar features.
[0040] The carbon-coated iron-based catalyst in the present invention will produce more olefins while catalyzing the hydrogenation of CO2 to produce higher alcohols. The present invention further converts olefins into aldehydes / alcohols in a series manner, which can further improve the production efficiency of higher alcohols and the utilization rate of carbon.
[0041] The carbon-coated iron-based catalyst of the present invention is prepared by the following method:
[0042] 1) Using nickel nitrate as a precursor, firstly, 0.5-3wt% of nickel was introduced into the above-mentioned ferric oxide by impregnation, and then, after drying and calcining at 400°C for 6h, a nickel-modified ferric oxide catalyst was obtained. Then, using potassium carbonate as a precursor, 0.5-5wt% of potassium was introduced into the nickel-modified ferric oxide by impregnation, and then, calcined at 350°C for 6h under flowing air (50mL / min).
[0043] 2) The material calcined at 350° C. was treated for 5 h at 10% (CO concentration in inert gas) CO / Ar (50 mL / min) and GHSV (Gas Hour Space Velocity) = 20,000 mL / g / h.
[0044] Exemplarily, the iron oxide used can be prepared by the following method:
[0045] 100 mL of 0.37 mol / L ammonium carbonate aqueous solution was added dropwise into 100 mL of 0.25 mol / L ferric nitrate solution under stirring at 70°C, and stirring was continued at 70°C for 2 h. The solution was then aged at room temperature for 6 h. After filtering, washing, and drying, the solution was calcined in a muffle furnace at 400°C for 4 h to obtain ferric oxide.
[0046] The following Experimental Examples 1 to 4 illustrate the effect of the carbon-coated iron-based catalyst of the present invention in catalyzing CO2 hydrogenation to produce higher alcohols alone.
[0047] Experimental Example 1
[0048] The carbon-coated iron-based catalyst has a potassium loading of 4wt% and a nickel loading of 0.5wt%, 1.0wt% and 3.0wt% respectively. After the carbonization treatment in the preparation of the carbon-coated iron-based catalyst is completed, when the temperature drops to the catalytic reaction temperature of 320°C, a reaction gas (24% CO2+72% H2) at 3.0MPa and a reaction space velocity of 8000mL / g / h (reaction gas flow rate of 20mL / min) is introduced for 15h.
[0049] The reaction products were continuously detected by online gas chromatography, and no catalyst deactivation was found during the reaction. The results showed that when the nickel loading was 0.5wt%, the CO2 conversion rate was 30.2%, the higher alcohol selectivity was 17.5%, and the higher alcohol space-time yield was 245.9mg / g / h; when the nickel loading was 1.0wt%, the CO2 conversion rate was 34.7%, the higher alcohol selectivity was 19.8%, and the higher alcohol space-time yield was 317.0mg / g / h; when the nickel loading was 3.0wt%, the CO2 conversion rate was 36.6%, the higher alcohol selectivity was 17.8%, and the higher alcohol space-time yield was 316mg / g / h.
[0050] Experimental Example 2
[0051] The carbon-coated iron-based catalyst has a potassium loading of 4wt% and a nickel loading of 1.0wt%, which are basically the same as those in Experimental Example 1, except that the reaction space velocities are 2000mL / g / h (reaction gas flow rate of 5mL / min) and 4000mL / g / h (reaction gas flow rate of 10mL / min), respectively.
[0052] The products after the reaction were continuously detected by online gas chromatography, and no catalyst deactivation was found during the reaction. When the reaction space velocity was 2000mL / g / h, the CO2 conversion rate was 40.1%, the higher alcohol selectivity was 15.6%, and the higher alcohol space-time yield was 246.0mg / g / h; when the reaction space velocity was 4000mL / g / h, the CO2 conversion rate was 36.3%, the higher alcohol selectivity was 17.8%, and the higher alcohol space-time yield was 262.0mg / g / h.
[0053] Experimental Example 3
[0054] It is basically the same as Experimental Example 2, except that the reaction space velocity is 8000 mL / g / h and the reaction time is 300 h.
[0055] The products after the reaction were continuously detected by online gas chromatography, and no catalyst deactivation was found during the reaction. The CO2 conversion rate was maintained at 32.5%, the higher alcohol selectivity was maintained at 19.8%, and the higher alcohol space-time yield was maintained at 317.0 mg / g / h.
[0056] Experimental Example 4
[0057] It is basically the same as Experimental Example 3, except that the carbon-coated iron-based catalyst is carbonized using potassium-modified ferric oxide, does not contain nickel, and has a potassium content of 4.0 wt%.
[0058] The products after the reaction were continuously detected by online gas chromatography. The space-time yield of higher alcohols was stable at 187 mg / g / h within 140 h, and then gradually decreased to 120 mg / g / h after 300 h, and the selectivity of higher alcohols was stable at 18% within 300 h.
[0059] The following is a detailed description of the cascade catalytic method for improving the catalytic efficiency of CO2 hydrogenation to produce higher alcohols provided by the present invention through Examples 1 to 3 and Comparative Examples 1 to 6.
[0060] Example 1
[0061] A tandem catalytic method for improving the catalytic efficiency of CO2 hydrogenation to produce higher alcohols, the method comprising:
[0062] The first stage reactor was filled with 150 mg of nickel / potassium modified ferric oxide (with a nickel content of 1.0 wt% and a potassium content of 4 wt%).
[0063] The second stage reactor was sequentially loaded with Rh / POLs (Rh: 0.1 wt%) hydroformylation catalyst and Cu / SiO2 (10 wt%) aldehyde hydrogenation catalyst.
[0064] Before the reaction, the catalyst loaded in the first reactor was carbonized under the conditions of 10% (CO concentration in inert gas) CO / Ar (50 mL / min), GHSV (Gas Hour Space Velocity, i.e., the volume of gas flowing over each gram of catalyst per hour) = 20000 mL / g / h, and the treatment time was 5 h.
[0065] After the above carbonization treatment is completed, the first stage reactor is cooled to the catalytic reaction temperature of 320°C, and 3.0MPa, 20mL / min reaction gas (24% CO2+72% H2) is introduced. At the same time, the second stage reactor needs to be heated to the reaction temperature of 150°C and react for 15h.
[0066] The products after the reaction were continuously detected by online gas chromatography, and no catalyst deactivation was found during the reaction. The results showed that the CO2 conversion rate was 33.7%, the selectivity of higher alcohols was 55.0%, of which methanol accounted for 2.5%, C 3+ The alcohol accounts for 75.5% (C3 alcohol 16.3%, C4 alcohol 35.9%, C5 alcohol 21.4%, C6 alcohol 1.9%). The space-time yield of higher alcohols is 1000 mg / g / h, the selectivity of olefins is 2%, and the selectivity of aldehydes is 2%.
[0067] The nickel / potassium modified ferric oxide used in this example is the catalyst in Experimental Example 1 with a potassium loading of 4 wt % and a nickel loading of 1.0 wt %.
[0068] The Rh / POLs (Rh: 0.1 wt%) catalyst preparation method used in this example is based on the work of Ding Yunjie, a researcher at the Dalian Institute of Chemical Physics, Chinese Academy of Sciences (Green Chem., 2016, 18, 2995-3005), which is obtained by solvent thermal reaction of tri(4-phenylethylene)phosphine and vinylbiphenyl.
[0069] The Cu / SiO2 catalyst was prepared by impregnation method. The specific process is as follows:
[0070] 1g of gas phase SiO2 (specific surface area 300m 2 / g) was added to 50mL aqueous solution containing 377.5mg Cu(NO3)2·3H2O, stirred for 24h, and then heated at 80℃ to remove water. The obtained powder was ground and calcined at 450℃ in a muffle furnace for 4h. The calcined sample was then reduced at 300℃ for 4h (10% H2 / Ar, 50mL / min).
[0071] Example 2
[0072] A tandem catalytic method for improving the catalytic efficiency of CO2 hydrogenation to produce higher alcohols, the method comprising:
[0073] The first stage reactor was loaded with 300 mg of zinc zirconium oxide / SAPO-34 composite catalyst.
[0074] The second stage is loaded with Rh / POLs (Rh: 0.1 wt%) hydroformylation catalyst and Cu / SiO2 (10 wt%) aldehyde hydrogenation catalyst. The preparation process of Rh / POLs and Cu / SiO2 catalysts is the same as that of Example 1.
[0075] The first stage reactor was pretreated at 400°C with Ar at a flow rate of 50 mL / min (normal pressure) for 2 hours. Then, the 50 mL / min Ar atmosphere was lowered to the catalytic reaction temperature of 380°C, and 3.0 MPa, 20 mL / min reaction gas (24% CO2 + 72% H2) was introduced. At the same time, the second stage reactor needed to be heated to a reaction temperature of 150°C. The reaction was carried out for 15 hours.
[0076] The products after the reaction were continuously detected by online gas chromatography, and no catalyst deactivation was found during the reaction. The results showed that the CO2 conversion rate was 13.5%, the olefin selectivity was 2%, the CO selectivity was 8%, the aldehyde selectivity was 3%, and the selectivity of higher alcohols was 74%, of which methanol accounted for less than 0.5%, and C 3+ The alcohol ratio is greater than 98% (C3 alcohol 43%, C4 alcohol 56%, C5 alcohol 2%). The space-time yield of higher alcohols reaches 360.4 mg / g / h.
[0077] The composite catalyst of zinc zirconium oxide / SAPO-34 used in this embodiment is prepared as follows:
[0078] 1) Preparation of zinc zirconium oxide by citric acid sol method
[0079] Dissolve 8.9g Zn(NO3)2·6H2O and 4.2g Zr(NO3)4·5H2O in 50mL water, then add 50mL citric acid monohydrate containing 18.4g, stir at room temperature for 30min, and then stir at 80℃ until gel is formed. The formed gel is calcined at 500℃ in a muffle furnace for 5h. The Zn / Zr in the oxide is 3 / 1.
[0080] 2) SAPO-34 was synthesized by hydrothermal method
[0081] First, tetraethylammonium hydroxide (TEAOH) and water were mixed evenly in a beaker, and aluminum isopropoxide powder was slowly added to the above solution and stirred vigorously until aluminum isopropoxide was completely hydrolyzed. Under vigorous stirring, a phosphoric acid solution with a mass fraction of 85% was added to the solution. After all the phosphoric acid was added, it was stirred vigorously for 2 hours. Finally, 40wt% silica sol was added dropwise and continued to stir for 1 hour to form a uniform solution. Finally, the obtained gel solution was transferred to a 100m reactor and crystallized at 170°C for 3 days. The obtained sample was repeatedly washed with deionized water and ethanol, and a solid sample was obtained by centrifugation. The solid sample was dried at 80°C overnight. Finally, the prepared solid was calcined at 600°C in a muffle furnace for 6 hours. The initial gel ratio (molar ratio) synthesized in the sample was: 1Al2O3 / 1.2P2O5 / 2.0TEAOH / 1SiO2 / 40H2O.
[0082] 3) Preparation of composite oxide catalysts
[0083] The zinc zirconium oxide and SAPO-34 were ground in a mortar at a mass ratio of 1:2 for 20 minutes.
[0084] Example 3
[0085] The same as Example 2, except that the second-stage hydroformylation catalyst is Rh / CeO2 (Rh: 0.1 wt%).
[0086] The first stage reactor was pretreated at 400°C with Ar at a flow rate of 50 mL / min (normal pressure) for 2 hours. Then, the 50 mL / min Ar atmosphere was lowered to the catalytic reaction temperature of 380°C, and 3.0 MPa, 20 mL / min reaction gas (24% CO2 + 72% H2) was introduced. At the same time, the second stage reactor needed to be heated to the reaction temperature of 170°C. The reaction was carried out for 15 hours.
[0087] The products after the reaction were continuously detected by online gas chromatography, and no catalyst deactivation was found during the reaction. The results showed that the CO2 conversion rate was 11.6%, the olefin selectivity was 16%, the CO selectivity was 21%, the aldehyde selectivity was 3%, and the selectivity of higher alcohols was 46%, of which methanol accounted for less than 0.5%, and C 3+ The alcohol ratio is greater than 98% (C3 alcohol 43%, C4 alcohol 56%, C5 alcohol 2%). The space-time yield of higher alcohols reaches 192.6 mg / g / h.
[0088] The Rh / CeO2 used in this embodiment is prepared by an impregnation method, as follows:
[0089] 2.03 mg RhCl3 was dissolved in 20 mL water, and then 1 g CeO2 was added. The mixture was stirred at room temperature for 30 min, and then ultrasonicated for 30 min. This cycle was repeated four times, and then stirred for 12 h. The resulting powder was then calcined at 400 ° C in a muffle furnace for 4 h. The calcined sample was then reduced at 250 ° C for 2 h (10% H2 / Ar, 50 mL / min).
[0090] Among them, CeO2 is prepared by a hydrothermal method, as follows:
[0091] 45 mL of an aqueous solution containing 28.8 g of NaOH was quickly added to 15 mL of an aqueous solution containing 3.14 g of Ce(NO3)3·6H2O and stirred vigorously for 30 min. The mixture was then treated in a hydrothermal reactor at 100°C for 24 h. The product was centrifugally washed and dried at 80°C for 12 h. The dried solid was calcined in a muffle furnace at 600°C for 4 h.
[0092] Comparative Example 1
[0093] It is basically the same as Example 1, except that:
[0094] The second stage reactor was not loaded with catalyst.
[0095] The products after the reaction were continuously detected by online gas chromatography, and no catalyst deactivation was found during the reaction. The results showed that the CO2 conversion rate was 33.7%, the selectivity of higher alcohols was 19.0%, of which methanol accounted for 6.1%, and C 3+ Alcohol accounts for 41.0%. Higher alcohol space-time yield is 317 mg / g / h, C 2-4 The olefin selectivity was 30.5%.
[0096] Comparative Example 2
[0097] It is basically the same as Example 1, except that:
[0098] The second stage reactor was loaded with Rh / POPs (Rh: 0.1 wt%) hydroformylation catalyst.
[0099] The products after the reaction were continuously detected by online gas chromatography, and no catalyst deactivation was found during the reaction. The results showed that the CO2 conversion rate was 33.7%, the selectivity of higher alcohols was 18%, of which methanol accounted for 5.7%, and C 3+ Alcohol accounts for 41.4%. The space-time yield of higher alcohol is 315 mg / g / h, the selectivity of olefins is 2%, and the selectivity of aldehydes is 29.0%. This shows that the olefins produced in the first stage are converted into corresponding aldehydes through the hydroformylation process, and the conversion efficiency can reach more than 90%.
[0100] Comparative Example 3
[0101] It is basically the same as Example 2, except that:
[0102] The second stage was loaded with Rh / POLs (Rh: 0.1 wt%) hydroformylation catalyst.
[0103] The products after the reaction were continuously detected by online gas chromatography, and no catalyst deactivation was found during the reaction. The results showed that the CO2 conversion rate was 13.1%, the olefin selectivity was 2%, the CO selectivity was 8%, and the aldehyde selectivity was 74%.
[0104] Comparative Examples 2 to 3 show that only aldehyde can be obtained without adding aldehyde hydrogenation catalyst in the second stage.
[0105] Comparative Example 4
[0106] It is basically the same as Example 2, except that:
[0107] The second stage was not loaded with catalyst.
[0108] The products after the reaction were continuously detected by online gas chromatography, and no catalyst deactivation was found during the reaction. The results showed that the CO2 conversion rate was 11.3%, the olefin selectivity was 39.0%, the CO selectivity was 44.0%, the methanol selectivity was 0.4%, and the remaining products were alkanes (16.6%). This shows that without the second stage hydroformylation catalyst, the CO and olefins produced in the first stage cannot be further converted.
[0109] Comparative Example 5
[0110] It is basically the same as Comparative Example 4, except that:
[0111] The zinc zirconium oxide used in the first stage has Zn / Zr=1 / 1.
[0112] The products after the reaction were continuously detected by online gas chromatography, and no catalyst deactivation was found during the reaction. The results showed that the CO2 conversion rate was 11.7%, the olefin selectivity was 45.8%, the CO selectivity was 43.1%, the methanol selectivity was 0.4%, and the rest was alkane (10.7%), which shows that the ratio of CO and olefin in the product can be adjusted by adjusting the Zn / Zr ratio of zinc zirconium oxide.
[0113] In the catalytic process of the zinc zirconium oxide / SAPO-34 composite catalyst, methanol and CO are produced on the ZnZr surface, and then methanol enters the SAPO-34 pores to produce olefins. If the ZnZr ratio is different, the ratio of methanol and CO produced is different. The 0.4% methanol in this example may be the part that is not completely converted in SAPO-34. The volume ratio of CO to olefins required for the hydroformylation process needs to be greater than 1, or CO is excessive, otherwise the hydroformylation process will not be effective.
[0114] Comparative Example 6
[0115] It is basically the same as Example 2, except that:
[0116] The zinc zirconium oxide used in the first stage has Zn / Zr=1 / 1.
[0117] The products after the reaction were continuously detected by online gas chromatography, and no catalyst deactivation was found during the reaction. The results showed that the CO2 conversion rate was 12.8%, the olefin selectivity was 24.2%, the CO selectivity was 21.5%, the aldehyde selectivity was 2.1%, and the selectivity of higher alcohols was 43.2%, of which methanol accounted for less than 0.4%, and C 3+ The alcohol ratio is greater than 98% (C3 alcohol 46%, C4 alcohol 53%, C5 alcohol 1%). The space-time yield of higher alcohols reaches 205.8 mg / g / h. This shows that adjusting the Zn / Zr ratio in zinc zirconium oxide to make the volume ratio of CO to olefins lower than 1 will affect the efficiency of the second stage hydroformylation, and then affect the efficiency of the formation of higher alcohols in the final product.
[0118] In summary, the tandem catalytic process of the present invention can efficiently catalyze the hydrogenation of CO2 into higher alcohols under suitable temperature and pressure conditions, wherein the CO2 conversion rate, the time-space yield and selectivity of higher alcohols are all high. Compared with the results reported in the literature, the tandem catalytic process of the present invention shows superior higher alcohol generation efficiency, especially high higher alcohol selectivity and carbon utilization. The invention can be used for the upgraded utilization of waste gas CO2 in power plants, coal chemical industry and other fields, and has very good application prospects.
[0119] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A tandem catalytic method for improving the catalytic efficiency of CO2 hydrogenation to produce higher alcohols, characterized in that: The method includes: Two fixed bed reactors are connected in series. The first reactor is filled with CO2 hydrogenation catalyst for olefins, and the second reactor is filled with olefin hydroformylation catalyst and aldehyde hydrogenation catalyst for alcohols.
2. The tandem catalytic method for improving the catalytic efficiency of CO2 hydrogenation to produce higher alcohols according to claim 1, characterized in that: The CO2 hydrogenation catalyst for olefin production is selected from any one or two of an iron-based hydrogenation catalyst and an oxide@SAPO-34 composite catalyst; When the catalyst contains an oxide@SAPO-34 composite catalyst, in the first stage reactor, CO2 is hydrogenated to produce olefins so that the volume ratio of the obtained CO to the olefins is controlled to be greater than 1.
3. The tandem catalytic method for improving the catalytic efficiency of CO2 hydrogenation to produce higher alcohols according to claim 2, characterized in that: The iron-based hydrogenation catalyst is selected from a carbon-coated iron-based catalyst; the iron-based catalyst is carbon-coated iron oxide loaded with alkali metal or alkali metal and nickel; wherein the nickel loading is 0-3wt% and the alkali metal loading is 0.5-5wt%; Or / and, the oxide@SAPO-34 composite catalyst is selected from zinc zirconium oxide@SAPO-34 composite catalyst.
4. The tandem catalytic method for improving the catalytic efficiency of CO2 hydrogenation to produce higher alcohols according to claim 3, characterized in that: In the carbon-coated iron-based catalyst, the alkali metal is selected from at least one of Li, Na, K, Rb and Cs.
5. The tandem catalytic method for improving the catalytic efficiency of CO2 hydrogenation to produce higher alcohols according to claim 3, characterized in that: The carbon-coated iron-based catalyst is obtained by the following method: The ferric oxide is impregnated and modified by an alkali metal salt, or the ferric oxide is impregnated and modified by a nickel salt and an alkali metal salt in sequence, and then an inert gas containing CO is introduced for reduction and carbonization treatment; or / and, the zinc-zirconium oxide@SAPO-34 composite catalyst is obtained by the following method: The zinc zirconium oxide and SAPO-34 are ground in a mass ratio of 1:
2.
6. The tandem catalytic method for improving the catalytic efficiency of CO2 hydrogenation to produce higher alcohols according to claim 5, characterized in that: The carbon-coated iron-based catalyst is obtained by the following method: Using nickel salt as a precursor, nickel is first introduced into ferric oxide by an impregnation method, and after drying and calcining at 400°C for 6 hours, a nickel-modified ferric oxide catalyst is obtained; then, using potassium salt as a precursor, potassium is introduced into the nickel-modified ferric oxide by an impregnation method, and then calcined at 350°C for 6 hours under flowing air conditions to obtain an iron-based catalyst; then, in an inert gas containing CO, a carbonization treatment is performed at 350°C for 5 hours to obtain a carbon-coated iron-based catalyst; Or / and, the zinc-zirconium oxide@SAPO-34 composite catalyst is obtained by the following method: 1) preparing zinc zirconium oxide by a citric acid sol method, wherein the molar ratio of Zn / Zr in the oxide is 3 / 1; 2) SAPO-34 was synthesized by a hydrothermal method: aluminum isopropoxide powder was slowly added to a tetraethylammonium hydroxide aqueous solution and stirred until the aluminum isopropoxide was completely hydrolyzed; under stirring, a phosphoric acid solution with a mass fraction of 85% was added to the solution; After all the phosphoric acid is added, the mixture is stirred for another 2 hours; finally, 40 wt% silica sol is added dropwise and stirred for another 1 hour to form a uniform solution; finally, the obtained gel solution is transferred to a reactor and crystallized at 170°C for 3 days; the obtained sample is repeatedly washed with deionized water and ethanol, and a solid sample is obtained by centrifugation; the solid sample is dried at 80°C; finally, the prepared solid is calcined at 600°C in a muffle furnace for 6 hours; 3) Grind zinc zirconium oxide and SAPO-34 in a mass ratio of 1:
2.
7. The tandem catalytic method for improving the catalytic efficiency of CO2 hydrogenation to produce higher alcohols according to claim 3, characterized in that: When the CO2 hydrogenation catalyst for preparing olefins is selected from a carbon-coated iron-based catalyst, an iron-based catalyst is installed in the first stage reactor, and the carbon-coated iron-based catalyst is obtained by carbonization treatment. When the temperature of the first stage reactor is controlled to be a catalytic reaction temperature of 300 to 350°C, a mixture of 3.0MPa, 2000 to 8000mL / g / hCO2 and H2 is introduced as a reaction gas for reaction; at the same time, the second stage reactor is heated to the desired reaction temperature; When the CO2 hydrogenation to olefin catalyst is selected from the oxide@SAPO-34 composite catalyst, the first-stage reactor is pretreated at 400°C by introducing Ar at a flow rate of 50 mL / min and normal pressure; then the temperature is reduced to 380°C in the catalytic reaction temperature under 50 mL / min Ar atmosphere, and a mixture of 3.0 MPa, 20 mL / min CO2 and H2 is introduced as the reaction gas for reaction; at the same time, the second-stage reactor is heated to the desired reaction temperature.
8. The tandem catalytic method for improving the catalytic efficiency of CO2 hydrogenation to produce higher alcohols according to claim 7, characterized in that: In the reaction gas, the volume ratio of CO2 to H2 is 1:
3.
9. The tandem catalytic method for improving the catalytic efficiency of CO2 hydrogenation to prepare higher alcohols according to claim 1, characterized in that: The olefin hydroformylation catalyst is selected from a phosphorus-containing polymer or an oxide-supported highly dispersed Rh catalyst, and the Rh loading amount is 0.1 wt%; Or / and, the aldehyde hydrogenation catalyst for preparing alcohol is selected from a Cu-based catalyst supported on an oxide carrier, and the active Cu loading is 10 wt%.
10. The tandem catalytic method for improving the catalytic efficiency of CO2 hydrogenation to produce higher alcohols according to any one of claims 1 to 9, characterized in that: The olefin hydroformylation catalyst and aldehyde hydrogenation catalyst are sequentially loaded into the second fixed bed and separated by inert fillers. The reaction temperature is 150-170° C. The raw material at the reactor inlet is the outlet gas of the first reactor. The reaction pressure and gas flow rate are the same as those of the first reactor.
Citation Information
Cited By
Fusarium oxysporum for saline-alkali soil and application of fusarium oxysporum
CN120796079A